Data from mass spectrometry, NMR spectra, GC–MS of fatty acid esters produced by Lasiodiplodia theobromae - Uranga, Carla C. (Data Brief, 2016)
The data described herein is related to the article with the title “Fatty acid esters produced by Lasiodiplodia theobromae function as growth regulators in tobacco seedlings” C.C. Uranga, J. Beld, A. Mrse, I. Cordova-Guerrero, M.D. Burkart, R. Hernandez-Martinez (2016) [1]. Data includes nuclear magnetic resonance spectroscopy and GC–MS data used for the identification and characterization of fatty acid esters produced by L. theobromae. GC–MS traces are also shown for incubations in defined substrate, consisting in Vogel׳s salts supplemented with either 5% grapeseed oil or 5% glucose, the two combined, or 5% fructose. Traces for incubations in the combination of 5% grapeseed oil and 5% glucose for different fungal species are also included. Images of mycelium morphology when grown in 5% glucose with or without 5% grapeseed oil are shown due to the stark difference in mycelial pigmentation in the presence of triglycerides. High concentration gradient data for the plant model Nicotiana tabacum germinated in ethyl stearate (SAEE) and ethyl linoleate (LAEE) is included to show the transition between growth inhibition and growth induction in N. tabacum by these compounds.